A novel calcium-independent cellular PLA2 acts in insect immunity and larval growth. (November 2015) - Park, Youngjin; Kumar, Sunil; Kanumuri, Rahul; Stanley, David; Kim, Yonggyun
Abstract: Phospholipase A2 (PLA2 ) catalyzes the position-specific hydrolysis of fatty acids linked to the sn -2 position of phospholipids (PLs). PLA2 s make up a very large superfamily, with more than known 15 groups, classified into secretory PLA2 (sPLA2 ), Ca 2+ -dependent cellular PLA2 (sPLA2 ) and Ca 2+ -independent cellular PLA2 (iPLA2 ). Only a few insect sPLA2 s, expressed in venom glands and immune tissues, have been characterized at the molecular level. This study aimed to test our hypothesis that insects express iPLA2, using the beet armyworm, Spodoptera exigua, our model insect. Substantial PLA2 activities under calcium-free condition were recorded in several larval tissue preparations. The PLA2 activity was significantly reduced in reactions conducted in the presence of a specific iPLA2 inhibitor, bromoenol lactone (BEL). Analysis of a S. exigua hemocyte transcriptome identified a candidate iPLA2 gene ( SeiPLA 2 -A ). The open reading frame encoded 816 amino acid residues with a predicted molecular weight of 90.5 kDa and 6.15 pI value. Our phylogenetic analysis clustered SeiPLA2 -A with the other vertebrate iPLA2 s. SeiPLA 2 -A was expressed in all tissues we examined, including hemocytes, fat body, midgut, salivary glands, Malpighian tubules and epidermis. Heterologous expression in Sf 9 cells indicated that SeiPLA2 -A was localized in cytoplasm and exhibited significant PLA2 activity, which was independent of Ca 2+ and inhibited by BEL. RNA interference (RNAi) of SeiPLA 2 -A using its specific dsRNA in the fifth instar larvae significantly suppressed iPLA2 expression and enzyme activity. dsSeiPLA2 -A-treated larvae exhibited significant loss of cellular immune response, measured as nodule formation in response to bacterial challenge, and extended larval-to-pupal developmental time. These results support our hypothesis, showing that SeiPLA2 -A predicted from the transcriptome analysis catalyzes hydrolysis of fatty acids from cellular PLs and plays crucial physiological roles in insect immunity and larval growth. Graphical abstract: Highlights: A Ca 2+ -independent phospholipase A2 (iPLA2 ) has been discovered in Spodoptera exigua. iPLA2 localizes to the cytosol and catalyzes phospholipid under EGTA. Suppression of iPLA2 impairs immune response and prevents larval growth.